A Predictive Model of Distance Instruction Integrating Considerations of Students, Teachers, and Instructional Contexts - Hsiu-Ping Yueh; Chaoyun Liang (Jiàoyù zīliào yǔ túshūguǎn xué, 2015)
This study examined the effects of learning ability, learning strategy, synchronism distance teaching, teaching effectiveness, and online-materials on the learning outcomes of engineering majors. The interaction between distance teaching and teaching effectiveness, as well as the mediating effects of online-materials were tested. The results indicated that the interaction between synchronism distance teaching and student evaluation of teaching effectiveness influenced online materials and student-perceived learning outcomes. The interaction effects of the group that highly valued distance instruction increased more in response to student evaluation of teaching effectiveness than did the effects of the group that valued distance instruction less. In addition, the results revealed that the quality of synchronism distance instruction, student evaluation of teaching effectiveness, and online materials are the keys to successful distance instruction. Among these critical factors, online materials played a mediating role in the relationship between the variables involved and student-perceived learning outcomes.